What does germane load mean? An empirical contribution to the cognitive load theory - Debue, Nicolas; van de Leemput, Cécile (Frontiers in Psychology, 2014)
While over the last decades, much attention has been paid to the mental workload in the field of human computer interactions, there is still a lack of consensus concerning the factors that generate it as well as the measurement methods that could reflect workload variations. Based on the multifactorial Cognitive Load Theory, our study aims to provide some food for thought about the subjective and objective measurement that can be used to disentangle the intrinsic, extraneous and germane load. The purpose is to provide insight into the way cognitive load can explain how users’ cognitive resources are allocated in the use of hypermedia, such as an online newspaper. A two-phase experiment has been conducted on the information retention from online news stories. Phase 1 (92 participants) examined the influence of multimedia content on performance as well as the relationships between cognitive loads and cognitive absorption. In Phase 2 (36 participants), eye-tracking data were collected in order to provide reliable and objective measures. Results confirmed that performance in information retention was impacted by the presence of multimedia content such as animations and pictures. The higher number of fixations on these animations suggests that users’ attention could have been attracted by them. Results showed the expected opposite relationships between Germane and Extraneous Load, a positive association between GL and cognitive absorption and a nonlinear association between Intrinsic and Germane Load. The trends based on eye-tracking data analysis provide some interesting findings about the relationships between longer fixations, shorter saccades and cognitive load. Some issues are raised about the respective contribution of mean pupil diameter and Index of Cognitive Activity.